Mergers and rivals' mark-ups: Evidence from European paper manufacturers - Rosen Marinov (Graduate Institute of International Studies, 2007)
This paper investigates the effect of merger-driven market concentration on the markups of non-merging rival firms in Europe's paper manufacturing industry. Using a representative data set of 400 independently-owned companies spanning a ten-year period, we aim to disentangle the impact of full-scale mergers and acquisitions from that due to other concentration-increasing developments. We find a positive and statistically significant relationship between price-cost margins and overall industry consolidation, as captured by the Herfindahl-Hirschman and four-firm indexes. However, takeover-related market share amalgamation has a negative impact, albeit of more modest proportions. The latter result seems to be driven by vertical transactions, suggesting that input-side channels, much as product price competition, may explain non-merging firms' mark-up response.
Keywords: C23; G34; K21; L11; 330; Mergers and acquisitions; Concentration; Mark-up; Competition policy; Übernahme; Marktmacht; Mark-up Pricing; Konzentrationsindex; Wettbewerbspolitik; Papierindustrie; Europa